Recommendations for lipid modification in patients with ischemic stroke or transient ischemic attack: A clinical guide by the Hellenic Stroke Organization and the Hellenic Atherosclerosis Society. Issue 6 (August 2021) - Sagris, Dimitrios; Ntaios, George; Georgiopoulos, Georgios; Kakaletsis, Nikolaos; Elisaf, Moses; Katsiki, Niki; Korompoki, Eleni; Kypreos, Kyriakos E; Boutari, Chrysoula; Bilianou, Helen; Makaritsis, Konstantinos; Nomikos, Tzortzis; et al.
This document presents the consensus recommendations of the Hellenic Stroke Organization and the Hellenic Atherosclerosis Society for lipid modification in patients with ischemic stroke or transient ischemic attack. This clinical guide summarizes the current literature on lipid management and can be of assistance to the physicians treating stroke patients in clinical practice.